SIMILARITIES AND DIFFERENCES OF VOICE IN ENGLISH AND UZBEK LANGUAGES. - Shamuratova Muhayyo Muzaffar qizi (TADQIQOTLAR.UZ, 2024)
Annotation: This article is devoted to the comparative study of active and passive voice systems in English and Uzbek languages. Focuses on the voices of both languages, showing and discussing commonalities and differences. This article is about identifying the similarities and differences between the most common active and passive voices of Uzbek students in English and the direct, reflexive, causative, passive and reciprocal voices in Uzbek.